Partial purication and characterization of recombinant alkalne protease. - Gayathri Selvaraju (2002)
The thermostable protease which synthesized by using recombinant E.Coli is partially purified by using heat treatment at 70 C for10 .20 and 30 minutes. The enzyme which was purified for the duration of 30 minutes has lowest protein content and highest protease activity. The intracellular enzyme has higher activity compared to the extracellular enzyme. The enzyme was partially purified 4-fold. The protein content of crude enzyme was higher than the partially purified enzyme. Yet. the enzyme activity of the partially purified enzyme is was higher than crude protease. SDS PAGE was carried out to confirm whether the sample is partially purified by observing the bands. The partially purified sample has lesser bands compared to the crude (control). Then, the characteristics that partially purified enzyme was studied. This enzyme has optimum temperature at 80 c with casein as substrate. Moreover, the optimum pH range is 8-10 but it could exhibit high activity at pH 10. Moreover. phenyl methane sulphonyl fluoride (PMSF) has inhibited the protease activity. But. it was not inhibited byth cEDaT_A÷:e a-Mercaptoethanol and SDS. in addition, the effect of metal ions was studied w_ +Z. Cu2`. Ag' and Fe' and Ca While, was able to increase the protease activity. 2 has little inhibitory effect on the protease activity but Cu2+, Ag` and Fe2 have high inhibitory effect on the protease activ\ty but they were not fully inhibited.